2011
DOI: 10.1007/s11481-011-9272-9
|View full text |Cite
|
Sign up to set email alerts
|

Morphine Potentiates Neuropathogenesis of SIV Infection in Rhesus Macaques

Abstract: Despite the advent of antiretroviral therapy, complications of HIV-1 infection with concurrent drug abuse are an emerging problem. Opiates are well-known to modulate immune responses by preventing the development of cell-mediated immune responses. Their effect on the pathogenesis of HIV-1 infection however, remains controversial. Using the Simian Immunodeficiency Virus/macaque model of HIV pathogenesis, we sought to explore the impact of morphine on disease progression and pathogenesis. Sixteen Rhesus macaques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
59
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 36 publications
(45 reference statements)
2
59
1
Order By: Relevance
“…These findings are consistent with studies demonstrating that treatment of SIV-infected rhesus macaques with selegiline, an inhibitor of dopamine catabolism through inhibition of MAO activity, or L-DOPA, the precursor of dopamine, resulted in elevated brain viral loads [73, 74]. In the SIV-macaque model, methamphetamine and opioid exposure increased both CSF/brain viral loads and macrophage influx into the CNS [75, 76]. In contrast, cocaine exposed SIV-infected macaques did not show elevated CNS viral replication or alterations in inflammatory markers; notably, the low dose cocaine-treated animals had significantly lower CSF viral RNA [77].…”
Section: Drug Abuse and Handsupporting
confidence: 85%
“…These findings are consistent with studies demonstrating that treatment of SIV-infected rhesus macaques with selegiline, an inhibitor of dopamine catabolism through inhibition of MAO activity, or L-DOPA, the precursor of dopamine, resulted in elevated brain viral loads [73, 74]. In the SIV-macaque model, methamphetamine and opioid exposure increased both CSF/brain viral loads and macrophage influx into the CNS [75, 76]. In contrast, cocaine exposed SIV-infected macaques did not show elevated CNS viral replication or alterations in inflammatory markers; notably, the low dose cocaine-treated animals had significantly lower CSF viral RNA [77].…”
Section: Drug Abuse and Handsupporting
confidence: 85%
“…As reported earlier, no significant differences were found in the CD4 or CD8 counts or plasma viral load between the V and VM groups (18). However, in other studies of SIV/SHIV-infected macaques, exposure to chronic morphine had a significant and dramatic effect on viral replication in cerebral tissues, resulting in early mortality (29,30). Furthermore, no correlation was observed between the plasma viral load/CD4 count and the degree of pulmonary vascular remodeling in these groups, although the C088 macaque, with the most pronounced arteriopathy, had the lowest CD4 counts among all of the animals.…”
Section: Discussionmentioning
confidence: 61%
“…Previous studies from our group have shown that morphine potentiates neuropathognesis in macaques infected with SIV mac R71/17E (Marcario et al, 2008; Bokhari et al, 2011). Such morphine mediated viral pathogenesis also resulted in alterations in brain stem responses and visual evoked potentials (Raymond et al, 1998; Cheney et al, 2008; Riazi et al, 2009).…”
Section: Discussionmentioning
confidence: 82%